The effect of ileostomy closure timing on low anterior resection syndrome in patient who underwent low anterior resection for rectal cancer - Kaka Ali, Hemn Hussain; Abdulkarim, Qalandar Hussein; Seerwan, Karzan; M .Salih, Barham M.; Hawramy, Omar H Ghalib; Mohammed, Dara Ahmed; Ahmed, Syamand Orhaman (Kurdistan Journal of Applied Research, 2021)
This is a multi-center retrospective study of patients underwent low anterior resection for rectal cancer. Ileostomy had been done to protect low lying Colo-rectal anastomosis, closure of ileostomy had been delayed in some patients due to patient own will, surgical complications (anastomotic leak) or coarse of chemotherapy. This study aimed to find the effect of temporary ileostomy on post-operative bowel defunction which is called Low anterior resection syndrome (LARS), and include; urgency, difficulty in emptying of bowel, and incontinence for feces and flatus. A total of 50 patients included in this study, the age ranges from the 19 to 80 years old with a mean age of 51.96 years. The total number of males was (33, %66). Majority of patients were overweight (21, 42%). The distance of tumors from the anal verge were less than 10 cm in (31,62%). The mean duration of fecal diversion was 7.17 months. Loop ileostomy were closed before six months in (27,54%). The mean duration of diversion of patients developed no LARS was 6.87 months which is shorter than those of developed LARS (7.31). Lower BMI patients are more prone to develop LARS, while Obese patients are more susceptible to develop major LARS. Nineteen cases developed LARS among those patient’s ileostomy closed before six months, and 15 cases developed LARS in those ileostomies closed after six months.